Students’ Strategies in Learning Speaking: Experience of Two Indonesian Schools - Syafryadin Syafryadin (Universitas Islam Negeri Walisongo Semarang, 2020)
The present study was an effort to investigate strategies mostly used in learning speaking, which covered direct strategies and indirect strategies. To this end, 60 students from two different high schools in a city in Indonesia, in which 30 students for each school participated this study. In collecting the data, this study used close-ended questionnaires with Strategy Inventory Language Learner (SILL) consisting of 39 items, which were analyzed by using a scoring system. The results of the study showed that students of both schools generally used the same and different learning strategies. The same learning strategies used by the students of both schools were organizing and evaluating learning, referring to metacognitive or indirect strategies. Meanwhile, the different learning strategies used by the students of both schools occurred on five strategies at a medium level. From the six types of learning strategies, as indicated in this study, the most popular learning strategies which were used by students of both schools were organizing and evaluating learning.